Digital Transformation Moderates AIS and CRM Impact on Business Sustainability - Afridayani, Afridayani; Habiiba Lavenia Qalammulloh; Sandra Lestari; Dewi Purnama Sari; Putri Daeng (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2025)
This study aims to examine the effect of the interaction between Accounting Information Systems (AIS) and Customer Relationship Management (CRM) on business sustainability, with digital transformation as a moderating variable. This research employs a quantitative approach by collecting primary data through structured questionnaires distributed to business owners and managers, particularly small and medium-sized enterprises (SMEs). The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to test the proposed hypotheses. The results indicate that Accounting Information Systems and Customer Relationship Management have a positive and significant effect on business sustainability. Furthermore, the interaction between AIS and CRM significantly enhances business sustainability, suggesting that the integration of internal financial information and customer-oriented systems strengthens long-term business performance. Digital transformation is found to moderate the relationship between AIS and CRM on business sustainability, indicating that higher levels of digital transformation strengthen the positive impact of AIS–CRM integration on business sustainability. This study contributes to the literature by providing empirical evidence on the strategic role of integrating accounting information systems and customer relationship management in achieving business sustainability, particularly in the context of digital transformation. The findings offer practical implications for business practitioners and policymakers in promoting digital-based system integration to enhance sustainable business performance.